The Effectiveness of Using Multiple Intelligences Learning Models on Biology Learning Outcomes of Class VII Students in Madani Junior High School of Makassar - Arwin Arif Win (Yayasan Ahmar Cendekia Indonesia, 2019)
The aim of this study was to determine the biology learning outcomes of Grade VII students of Madani Junior High School of Makassar on the subject of diversity of living creatures that were learned with the Multiple Intelligence learning models. This type of research is quasi-experimental (quasi-experimental) using a pretest-posttest nonequivalent control group design. The population of this study were all VII grade students of Madani Junior High School of Makassar in the 2018/2019 school year consisting of 3 study groups totaling 67 students with a sample of 21 people in class VII2 and 21 people in class VII1.The results showed that the value of sig.count was 0.889 with sig.table (α) of 2.021. Thus it is clearly seen that the value of sig.calculate (0.889) <sig.table (2.021), means that H0 is rejected H1 is accepted, meaning it can be concluded that the biology learning outcomes of students taught by the Multiple Intelegences learning model have a positive effect on the material diversity of living things in Madani Junior High School of Makassar.